KESANTUNAN BERBAHASA DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VII SMP MAKASSAR MULYA: Language Politeness in Indonesian Language Learning for Students of Class VII Smp Makassar Mulya - Armadani, A. Kartika; Usman; Wijayanti, Tuti (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to describe the forms of linguistic politeness used by students towards teachers in Indonesian language learning interactions in Grade VII at Makassar Mulya Junior High School. Using a qualitative descriptive approach, data were collected through recording, transcription, and note-taking techniques. The analysis was conducted using a qualitative descriptive method that included tabulation, presentation, interpretation, and conclusion drawing. The results of the study indicate that the teachers' linguistic politeness towards students includes the use of declarative, interrogative, imperative, and exclamatory sentences that comply with various maxims such as prudence, simplicity, agreement, and sympathy. Meanwhile, the students' politeness towards teachers also follows similar maxims, with the addition of the maxim of appreciation in exclamatory sentences. Overall, the students' linguistic politeness falls into the polite category.